Cooperative action and compatibility between Portland cement and MSWI bottom ash alkali-activated double gel system materials. (10th June 2019) - Huang, Guodong; Yuan, Liang; Ji, Yongsheng; Liu, Benlin; Xu, Zhishan
Highlights: Double gel system materials has a severe incompatibility problem. Layered casting can achieve the compatibility of double gel system materials. Interface transition zone in double gel system materials can be enhanced. Abstract: This study investigated the cooperative action and compatibility between Portland cement and municipal solid waste incineration (MSWI) bottom ash alkali-activated double gel system materials, focusing on the two different methods of mixed casting and layered casting. The results show that alkali-activated materials and Portland cement have a severe incompatibility problem when mixed casting is used. However, layered casting completely solves this compatibility problem in double gelled system materials. This is because liquid sodium silicate accelerates the initial setting time in alkali-activated materials and thus eliminates the influence between polymerization and hydration. Furthermore, alkali-activated materials can compensate for the lack of calcium by absorbing the Ca(OH)2 generated by the hydration of Portland cement. In this case, Calcium-Silicate-Hydrate (C-S-H) and Aluminium-Modified Calcium-Silicate-Hydrate (C-A-S-H) gels are formed, which strengthens the interface transition zone.